Generating (2,3)-codes - Anisimov, A.V. (Кибернетика и системный анализ, 2020)
The (2,3)-representation of integers utilizes the mixed numeration base of the radix-2 and the auxiliary radix-3. This representation yields a universal prefix-free binary encoding of all natural numbers with a variety of useful properties: robustness (self-synchronization), local error corrections, statistic regularities of code parameters, etc. The paper describes a procedure of monotonic generation of (2,3)-codewords in ascending order of their lengths.